Correlation between crash avoidance maneuvers and injury severity sustained by motorcyclists in single-vehicle crashes. (17th February 2016) - Wang, Chen; Lu, Linjun; Lu, Jian; Wang, Tao
ABSTRACT: Objectives : In order to improve motorcycle safety, this article examines the correlation between crash avoidance maneuvers and injury severity sustained by motorcyclists, under multiple precrash conditions.Method : Ten-year crash data for single-vehicle motorcycle crashes from the General Estimates Systems (GES) were analyzed, using partial proportional odds models (i.e., generalized ordered logit models).Results : The modeling results show that "braking (no lock-up)" is associated with a higher probability of increased severity, whereas "braking (lock-up)" is associated with a higher probability of decreased severity, under all precrash conditions. "Steering" is associated with a higher probability of reduced injury severity when other vehicles are encroaching, whereas it is correlated with high injury severity under other conditions. "Braking and steering" is significantly associated with a higher probability of low severity under "animal encounter and object presence, " whereas it is surprisingly correlated with high injury severity when motorcycles are traveling off the edge of the road. The results also show that a large number of motorcyclists did not perform any crash avoidance maneuvers or conducted crash avoidance maneuvers that are significantly associated with high injury severity.Conclusions : In general, this study suggests that precrash maneuvers are an important factor associated with motorcyclists' injury severity. To improve motorcycle safety, training/educational programs should be considered to improve safety awareness and adjust driving habits of motorcyclists. Antilock brakes and such systems are also promising, because they could effectively prevent brake lock-up and assist motorcyclists in maneuvering during critical conditions. This study also provides valuable information for the design of motorcycle training curriculum.